-2c+10=-3c-4-c

Simple and best practice solution for -2c+10=-3c-4-c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2c+10=-3c-4-c equation:



-2c+10=-3c-4-c
We move all terms to the left:
-2c+10-(-3c-4-c)=0
We add all the numbers together, and all the variables
-2c-(-4c-4)+10=0
We get rid of parentheses
-2c+4c+4+10=0
We add all the numbers together, and all the variables
2c+14=0
We move all terms containing c to the left, all other terms to the right
2c=-14
c=-14/2
c=-7

See similar equations:

| 6x-11/8=2x-13/8 | | 1/3x^2+4=16 | | 30=-16t^2+128t | | -9.11-8.2y=8.09-6.2y | | 6x^2+4=-36 | | g-141=148 | | 361x+34=1 | | 2(3x+1)=4(x–1) | | 6d+108+7d+112=90 | | 7.65=2.25+0.20(m=1) | | 19m+3=28.6 | | 3x=18;×= | | 1,800,000=x*(1*06)^35 | | 3m+19=28.60 | | 3m+19=28.6 | | 1,800,000=x*1.06^35 | | 1,800,000=x*(1.06)^35 | | 9.95+3.7n=-9.76+5.3n-4.3n | | 45x.50x=2x | | 11a+24=42 | | 1.3(8–b)+3.7b=−5.2 | | 2f+10=-8-f | | -9v-8=-4v-6v+1 | | -5+2(5+4a)=-43 | | (5x+3)(4x+8)=146 | | 2m+3.10=21.10 | | -6.7p+7.89=-7.7p+7.89 | | 400+t=620 | | 7u-10=9u+10 | | 24x+9=96 | | 5.86-4.9n=-3.92-6.3n+1.94 | | 27/2.5=18/p |

Equations solver categories